Ear Screening Findings among Children Attending Staff Schools of Ahmadu Bello University, Zaria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background/Aims:Ear disease in children is a major public health concern in developing countries. World Health Organization suggests external ear examination for all school entrants in developing countries to identify those with ear discharge and study the extent of ear diseases in the community. The aim of this survey is to screen ears of children attending Ahmadu Bello University staff schools, Zaria and to document the findings.Materials and Methods:This was a cross-sectional survey conducted at four staff schools of Ahmadu Bello University, Zaria between March and May 2013. One thousand and nineteen (1019) consecutive children aged 4–15 years from primary 1 to junior secondary school 3 (JSS 3) were included in this survey. All students were interviewed for the presence or absence of various symptoms of ear diseases followed by ear examination.Results:This survey included 1019 participants, of which 511 (50.1%) and 508 (49.9%) were males and females, respectively. The mean age and standard deviation were 9 and 2.53, respectively. Three hundred and eighty-two (37.5%) of the study population had otologic diseases whereas 637 (62.5%) did not. Impacted wax was the most common otologic disorder observed in 297 (29.1%) followed by otitis media with effusion (tentatively) 43 (4.2%), otomycosis 11 (1.1%), chronic suppurative otitis media 9 (0.9%), preauricular sinus (0.9%), and otitis externa 6 (0.6%).Conclusion:This survey highlights that ear diseases are common among children. Periodic ear examination and health education are essential.